Humanist Librarians in the AI Era : Maintaining Human Values in Information Services - Azwar Azwar (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
The development of artificial intelligence (AI) technology has brought about a major transformation in the world of libraries and information services. Automation, data analysis, and AI-based recommendation systems have increased the efficiency and accessibility of information for users. These advances also pose new challenges for librarians, particularly in maintaining human values ​​in the service process. Humanist librarians in the AI ​​era are required not only to understand technology but also to maintain an ethical, empathetic, and communicative role in interactions with users. This research uses a literature review to address the questions raised. Librarians, as mediators between technology and humans, act as bridges between digital literacy and ethical information, maintaining warmth and empathy in library services. By prioritizing human values ​​such as empathy, responsibility, and information justice, librarians can ensure that the application of AI in libraries remains oriented toward human needs and does not diminish the essence of civilized service.